Letter : International Brigade Association - Young, James
035-0065-001 The Association of Engineering and Shipbuilding Draughtsmen General Secretary: JAMES YOUNG Registered Office: ST. GEORGE'S SQUARE, LONDON, S.W.1. Telegraphic Address: "DRAFTINEER, SOWEST, LONDON." Telephone - Victoria 0747 and 0748 Registered under T.U. Acts No. 1691 T. Please address all Communications for Head Office to "THE GENERAL SECRETARY." Your Ref. International VT/EAB/EM/113. THIS REFERENCE MUST BE QUOTED IN REPLYING TO THIS LETTER Ref. JY/HA/TUC/G. 26th October, 1948 The General Secretary, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Mr. Tewson, International Brigade Association I have to thank you for your letter of the 25th inst., and note your remarks regarding the above organisation. Yours sincerely, James Young, General Secretary. 292/946/35/65